Hydroxyethyl cellulose matrix applied to serial crystallography - Michihiro Sugahara (Nature Portfolio, 2017)
Serial femtosecond crystallography (SFX) allows structures of proteins to be determined at room temperature with minimal radiation damage. A highly viscous matrix acts as a crystal carrier for serial sample loading at a low flow rate that enables the determination of the structure, while requiring consumption of less than 1 mg of the sample. However, a reliable and versatile carrier matrix for a wide variety of protein samples is still elusive. Here we introduce a hydroxyethyl cellulose-matrix carrier, to determine the structure of three proteins. The de novo structure determination of proteinase K from single-wavelength anomalous diffraction (SAD) by utilizing the anomalous signal of the praseodymium atom was demonstrated using 3,000 diffraction images.